A CASE FOR A LONGER TERM OF COPYRIGHT IN CANADA - IMPLICATIONS OF ELDRED V. ASHCROFT - Ahmed, Kamil (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 2006)
In 1993, a European Union ("EU") directive instructed EU members to extend their baseline term of copyright by 20 years, to 70 years subsequent to an author's death, and to deny the longer term of copyright to non-EU nation-states that do not provide the same extended term. This directive has spearheaded legislative change throughout the world. The United States ("US") Congress adopted the Copyright Term Extension Act in 1998, which extended the term of all existing and future copyrights by 20 years. The US Supreme Court affirmed the legality of the Copyright Term Extension Act in Eldred v. Ashcroft in 2003. A life plus 70 year copyright term in the EU and US has marked repercussions for Canada, whose Copyright Act still prescribes a life plus 50 year term. This paper argues that Parliament must not ignore copyright law developments in the EU and US, and should amend the Canadian Copyright Act to extend the term of copyright to a life plus 70 term. In its deliberations, Parliament must consider protecting the interests of Canadian copyright holders who commercially exploit their works internationally. The potential cost savings resulting from the harmonization of Canada's copyright laws to that of its trading partners, the likely chilling effect on innovation in Canada given the longer terms of copyright in other nation-states, in addition to demographics and technology are all compelling factors supporting a longer term of copyright.